2018
DOI: 10.1016/s2468-2667(17)30222-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of cervical cancer incidence in England, UK, up to 2040, under four scenarios: a modelling study

Abstract: SummaryBackgroundIn the next 25 years, the epidemiology of cervical cancer in England, UK, will change: human papillomavirus (HPV) screening will be the primary test for cervical cancer. Additionally, the proportion of women screened regularly is decreasing and women who received the HPV vaccine are due to attend screening for the first time. Therefore, we aimed to estimate how vaccination against HPV, changes to the screening test, and falling screening coverage will affect cervical cancer incidence in Englan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 24 publications
(24 reference statements)
2
37
0
Order By: Relevance
“…31 We found that the annual age-standardised incidence of cervical cancer in Australia is predicted to plateau below a potential elimination threshold (at four cases per 100 000 women) if cohorts offered the nonavalent vaccine do not receive cervical screening. Our medium-term predictions for the incidence of cervical cancer are similar to estimates published for England, 32 which found that primary HPV screening and vaccination with the nonavalent vaccine (with screening coverage and vaccine uptake assumptions in women similar to those that we used in this analysis) is likely to reduce the annual age-standardised incidence of cervical cancer and the associated mortality rate in England by 28% in 2036-40 compared with estimates of incidence over the same time period in which cytology every 3 years and vaccination against only HPV types 16 and 18 were used. Our results are broadly consistant with this finding, since we found that scenarios that assumed a transition to the renewed NCSP showed an age-standardised incidence of cervical cancer that was 33% lower than if the pre-renewed NCSP had been maintained (as previously published).…”
Section: Discussionsupporting
confidence: 84%
“…31 We found that the annual age-standardised incidence of cervical cancer in Australia is predicted to plateau below a potential elimination threshold (at four cases per 100 000 women) if cohorts offered the nonavalent vaccine do not receive cervical screening. Our medium-term predictions for the incidence of cervical cancer are similar to estimates published for England, 32 which found that primary HPV screening and vaccination with the nonavalent vaccine (with screening coverage and vaccine uptake assumptions in women similar to those that we used in this analysis) is likely to reduce the annual age-standardised incidence of cervical cancer and the associated mortality rate in England by 28% in 2036-40 compared with estimates of incidence over the same time period in which cytology every 3 years and vaccination against only HPV types 16 and 18 were used. Our results are broadly consistant with this finding, since we found that scenarios that assumed a transition to the renewed NCSP showed an age-standardised incidence of cervical cancer that was 33% lower than if the pre-renewed NCSP had been maintained (as previously published).…”
Section: Discussionsupporting
confidence: 84%
“…First, we assumed that there are no cohort effects. This may bias estimates of the absolute CIN3+ risk but the effect on the relative decline in risk is likely to be small 46 as we found little association between type distribution and age 47 . The absolute CIN3+ risk may be somewhat underestimated because recently the cervical cancer incidence has increased in the Netherlands, in particular in young women 48 .…”
Section: Discussionmentioning
confidence: 80%
“…However, China still has a long way to go before cervical cancer is eliminated. In contrast to the reducing cervical cancer incidence and mortality trends in developed countries [4], a substantial increase in incidence and mortality was seen in China [2]. Multiple factors have been identified as contributors to the incidence of cervical cancer in developing regions of the world, such as lack of vaccines, lack of cervical screening programs, poor treatment services, and high HPV infection [5].…”
Section: Introductionmentioning
confidence: 99%